The Madagascar International Cooperative Biodiversity Group (ICBG): Using Natural Products Research to Build Science Capacity - Miller, James S.; Birkinshaw, Christopher; Callmander, Martin (Ethnobotany Research and Applications, 2005)
In 1993, the National Institutes of Health funded a program to support multi-institutional partnerships to conduct natural products drug discovery in a manner to support conservation and economic growth. To date, ten International Cooperative Biodiversity Groups (ICBG) have been supported. The activities of the Madagascar ICBG project are reviewed, first providing an overview of goals of the program to conduct botanical inventory, conservation analysis, and to collect samples for bioassay in Madagascar’s northern complex, then focusing on efforts to build capacity to conduct these activities within Madagascar. This paper introduces the results of a recently conducted ethnobotanical training program.